S'gor water restructuring agreement not affected by change in MB - Borneo Post, (KK) (BorneoPost, 2014)
KUALA LUMPUR: The signing of the 'Heads of Agreement' on restructuring of the Selangor water industry cannot be annulled by a change of the Selangor Menteri Besar.